Cognitive and emotional changes in patients with juvenile myoclonic epilepsy - R. V. Magzhanov; D. V. Anisimova; P. N. Vlasov; V. A. Petrukhin; E. B. Tsevtsivadze; S. R. Nurmukhametova (Неврология, нейропсихиатрия, психосоматика)
Objective: to reveal the prevalence of cognitive impairment and emotional disorders (anxiety and depression) in patients with juvenile myoclonic epilepsy (JME) and to evaluate the role of a hormonal background, taken antiepileptic drugs (AEDs), and the course of the disease in the genesis of found abnormalities.Patients and methods. The prevalence of cognitive impairment and emotional-affective disorders was analyzed in 48 female patients with JME.Results and discussion. Decreased cognitive functions according to the Montreal Cognitive Assessment were detected in 12 (40%) patients. The greatest difficulties were faced by the patients when they carried out the tasks used to examine memory and abstract thinking. The level of anxiety and depression was assessed using the Hospital Anxiety and Depression Scale (HADS) and the Beck Depression Inventory (BDI). The HADS showed the subclinical manifestations of depression in 10 (33.3%) patients and their obvious ones in 4 (13.4%). The subclinical manifestations of depression, assessed by HADS scores, were detected in 4 (13.3%) patients; its obvious manifestations were absent. BDI scores indicated that there were minimal, mild, moderate, and severe manifestations in 6 (20%), 3 (10%), 2 (6.7%), and 1 patients, respectively. Cognitive functions and the level of anxiety and depression did not depend on the patients’ age at disease onset and at the time of investigation, disease duration, menstrual cycle regularity, therapy regimen, and hormonal status. However, all the patients tended to have lower estradiol and higher progesterone and testosterone levels as cognitive and emotional disorders increased. Myoclonic seizures in conjunction with generalized tonic-clonic seizures significantly more frequently led to cognitive and emotional-affective disorders. Cognitive and emotional disorders occurred in patients without remission and depended on the nature of seizures. The absence of differences between the groups of patients treated with various antiepileptic drugs (AEDs) is due to the fact that most patients received valproates (n = 19) or monotherapy (n = 26), and the number of patients taking other AEDs proved to be incomparably small.